Unravelling the complexities in high-grade rocks using multiple techniques : the Achankovil Zone of southern India - Taylor, Richard; Clark, Christopher; Johnson, Tim; Santosh, M.; Collins, A. (Springer, 2015)
The Achankovil Zone of southern India forms a distinct isotopic and structural boundary separating the Madurai Block to the north from the Trivandrum Block to the south. We combine isotopic and trace element geochemistry of major and accessory phases with phase equilibria modelling to provide quantitative constraints on the timing and conditions of peak metamorphism and the nature of the protoliths within the Achankovil Zone. The results suggest a clockwise pressure–temperature path with peak metamorphic temperatures of up to 950 °C at pressures of around 0.7 GPa followed by high temperature decompression. The metamorphic peak occurred at 545–512 Ma. U–Pb and Hf isotopic analysis of detrital zircon shows the rocks have a strong affinity with the southern part of the Madurai Block. The Achankovil Zone is interpreted as the reworked southern margin of the Madurai Block, which was metamorphosed during the final stages of the assembly of Gondwana.